Upaya Meningkatkan Karakter Siswa Melalui Manajemen Iklim Budaya Sekolah di SMP dan SMA Kabupaten Bandung Barat - Ayi Najmul Hidayat; Kingking Muttaqien; Gatot Yusuf Effendi (LPPM UNINUS, 2017)
A lack of character education achievement in high school is due to the weakness of school culture climate management. Junior and Senior High School students have potency to develop their character, and the teacher also has a wide opportunity to improve the character education of students.One of them is by improving the conducive school culture climate management. Character education really needs to be improved in school. Therefore, the this training purpose is to work out BK coordinators/counselors so as they can improve school culture climate management,as well asboth characters of junior high and high school students. The methods in this training are: discussion, lecture, and demonstration (or) practice. The training result can improve the teachers’ spirit to understand and implement the school culture climate management and teachers’ willing to follow the next training. The teachers’ spirit itself will support the success of improving character education in schools. This training can develop teachers' skills and motivate students to engage in creating condition that enhance character educationdirectly. School culture climate management in accordance with school condition will facilitate the implementation of character education on both junior and senior high school students.